2015
DOI: 10.3390/ma8105346
|View full text |Cite
|
Sign up to set email alerts
|

Rice Husk Ash to Stabilize Heavy Metals Contained in Municipal Solid Waste Incineration Fly Ash: First Results by Applying New Pre-treatment Technology

Abstract: A new technology was recently developed for municipal solid waste incineration (MSWI) fly ash stabilization, based on the employment of all waste and byproduct materials. In particular, the proposed method is based on the use of amorphous silica contained in rice husk ash (RHA), an agricultural byproduct material (COSMOS-RICE project). The obtained final inert can be applied in several applications to produce “green composites”. In this work, for the first time, a process for pre-treatment of rice husk, before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Upon burning, cellulose and lignin are removed from RH, leaving behind silica ash. Indeed, the chemical composition of RHA has demonstrated that nearly 90% is composed by SiO 2 , and the other part by metal oxides, such as Al 2 O 3 , MgO, Fe 2 O 3 , CaO, Na 2 O, and K 2 O [24,[33][34][35][36][37][38]. The relevant amount of SiO 2 makes this kind of ash highly porous and lightweight, with a very high external surface area.…”
Section: Rice Husk Ash (Rha)mentioning
confidence: 99%
“…Upon burning, cellulose and lignin are removed from RH, leaving behind silica ash. Indeed, the chemical composition of RHA has demonstrated that nearly 90% is composed by SiO 2 , and the other part by metal oxides, such as Al 2 O 3 , MgO, Fe 2 O 3 , CaO, Na 2 O, and K 2 O [24,[33][34][35][36][37][38]. The relevant amount of SiO 2 makes this kind of ash highly porous and lightweight, with a very high external surface area.…”
Section: Rice Husk Ash (Rha)mentioning
confidence: 99%
“…Because the cost of this process is high, being dependent on the colloidal silica quotation, recently the technology was improved by the substitution of commercial silica with rice husk ash (RHA), an agricultural by product of rice cultivation ( Benassi et al, 2015a ; Bosio et al, 2014a ). This project, named COSMOS-RICE, has already shown the capability to produce new fillers, by using stabilized waste ( Ponsot et al, 2015 ; Benassi et al, 2015b ; Bosio et al, 2014b ; Besco et al, 2014 ; Zacco et al, 2012 ; Besco et al, 2013 ), that were inserted in polypropylene, polyethylene, nylon, some resins and ceramics. It is possible to obtain attractive and sustainable products that can compete with the market of natural raw materials on the global stage.…”
Section: Introductionmentioning
confidence: 99%
“…MSWI-FA is generally considered the most problematic incineration waste, due to the presence of leachable heavy metals [3]. Several technologies for MSWI-FA stabilization have been already proposed [4][5][6][7][8] with the aim to promote its reuse [9][10][11]. Even though some recently proposed MSWI-FA treatments were defined as zero-waste technologies [12], they often require MSWI-FA pre-treatments, which need the use of some additional processes and raw materials.…”
Section: Introductionmentioning
confidence: 99%